2018
DOI: 10.1186/s13075-018-1552-9
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate upregulates circadian transcriptional factors PAR bZIP to induce apoptosis on rheumatoid arthritis synovial fibroblasts

Abstract: BackgroundEffects of methotrexate (MTX) on the proliferation of rheumatoid arthritis (RA) synovial fibroblasts are incompletely understood. We explored actions of MTX in view of circadian transcriptions of synovial fibroblasts.MethodsUnder treatment with MTX, expression of core circadian clock genes, circadian transcriptional factor proline and acidic amino acid-rich basic leucine zipper (PAR bZIP), and proapoptotic molecule Bcl-2 interacting killer (Bik) was examined by real-time polymerase chain reaction. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The influence of pharmacotherapy on the gene expression levels have been further researched in the previous studies [25,26]. Therefore, mRNA expression levels of ROR-γt and other transcription factors in our study might be influenced by medications taken by patients with refractory RA who underwent MSCT.…”
Section: Gene Expression Levelsmentioning
confidence: 76%
“…The influence of pharmacotherapy on the gene expression levels have been further researched in the previous studies [25,26]. Therefore, mRNA expression levels of ROR-γt and other transcription factors in our study might be influenced by medications taken by patients with refractory RA who underwent MSCT.…”
Section: Gene Expression Levelsmentioning
confidence: 76%
“…Hepatic leukemia factor (HLF) is a circadian gene that belongs to the family of the proline and acidic amino acid-rich basic leucine zipper transcription factors (PAR bZIP) [ 40 , 41 ]. Previous studies have demonstrated that HLF plays an essential physiological role in nervous system development [ 42 ], as well as in fibroblast apoptosis [ 43 ]. Moreover, the aberrant expression of HLF was found to extensively participate in the various processes of tumorigenesis; HLF was found to be downregulated in glioma and may promote the proliferation, metastasis, and radiosensitivity of cancer cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have clarified the mechanism of MTX-induced apoptosis. MTX upregulates the circadian transcriptional factor proline-and acidic amino acid-rich basic leucine zipper, resulting in RA-FLS apoptosis [72]. TNF inhibitors also induce apoptosis in RA-FLS [73,74].…”
Section: Macrophages Monocytes and Flsmentioning
confidence: 99%